Pelaksanaan good agricultural practices dan penerapan skema fair trade pada perkebunan kopi rakyat Jawa Tengah - Supriatno (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The implementation of Good Agricultural Practices (GAP) on smallholder coffee plantations in Central Java is considered a solution that has the potential to increase coffee production while protecting biodiversity and achieving sustainable plantations. Several preliminary studies show that implementing GAP is directly proportional to the productivity of crops and prevents monoculture plantation methods, which are detrimental to the environment and productivity. Apart from that, another problem being addressed is the low welfare of coffee farmers in Central Java due to the low purchasing price of coffee and the dominant export in the form of raw coffee beans. This province can take steps by introducing a fair trade scheme for coffee farmers who are members of cooperatives or farmer groups. By implementing fair tradeprinciples, farmers' welfare can increase through equal welfare distribution between farmers and sellers, price transparency, new business opportunities, decent wages for workers, and environmentally friendly production and sales processes. Through analysis of the two problems above, this article aims to provide a deeper understanding of the importance of implementing GAP and fair trade schemes in increasing the productivity and welfare of coffee farmers in Central Java, as well as contributing to the development of sustainable and environmentally sound coffee plantations in Indonesia.